"Economic growth is a vital catalyst for reducing poverty and ensuring sustainable development." (Texas Journal of Multidisciplinary Studies, 2024)
Economic growth is an important tool for poverty reduction and sustainable development. It is an important factor influencing social investment, empowering individuals and promoting inclusion, safety nets and the eradication of multidimensional poverty. This article discusses how economic growth can contribute to poverty reduction efforts and accelerate the achievement of the Sustainable Development Goals (SDGs). We also consider the importance of data and measurement in monitoring progress and developing global partnerships for sustainable development